Climate change and technological options : - Soyez, Konrad (SpringerWien, 2008)
An up-to-date text on climate change focussing on technical solutions for the most important and climate relevant economic sectors is presented. It is intended for key decision makers, and administrators within industry, agricultural and energy sectors, as well as masters students and post graduates. The first of three sections covers the scientific basis of climate change and the instruments to prevent or reduce negative climate effects. It includes a survey covering current practices at different levels. The second discusses evaluation methods for climate impacts from industrial processes. Climate relevant processes and measures to reduce their impact such as sequestration are defined in the final section, with the main focus being on renewable resources. Details are given on climate impacts of waste prevention, recycling and waste management as well as are proposals for every day solutions.